2017
DOI: 10.7748/ns.2017.e10874
|View full text |Cite
|
Sign up to set email alerts
|

Errors in the nursing management of a deteriorating patient

Abstract: Effective management of the deteriorating patient requires early recognition of the signs of deterioration, timely review and appropriate interventions. However, this does not always occur. Errors in the recognition and management of a deteriorating patient are rarely related to a single factor; rather they are a complex interaction of system and human factors. This article presents a case study focusing on understanding the factors that led to errors resulting in the death of a patient. Understanding the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…factors contributing to a patient's death in the case study discussed by Gluyas. 9 In that study, it was identified that documentation on the vital signs observation charts used in the facility did not denote parameters outside normal limits and the chart did not detail protocols for escalation. Keene et al 17 state that EWS are effective in monitoring patients; however, the EWS efficacy is dependent on the accuracy and quality of vital sign documentation.…”
Section: Documentationmentioning
confidence: 99%
See 4 more Smart Citations
“…factors contributing to a patient's death in the case study discussed by Gluyas. 9 In that study, it was identified that documentation on the vital signs observation charts used in the facility did not denote parameters outside normal limits and the chart did not detail protocols for escalation. Keene et al 17 state that EWS are effective in monitoring patients; however, the EWS efficacy is dependent on the accuracy and quality of vital sign documentation.…”
Section: Documentationmentioning
confidence: 99%
“…The proactive approach is more of a wait-and-see tactic when dealing with patients with abnormal vital signs. 16 In a case study involving an unexpected patient death, Gluyas 9 reported that a coroner's recommendation was to implement an early warning scoring system with structured communication protocols as the chart in use at that time was not designed to identify observations outside normal limits and did not detail how concerns could be escalated in a timely manner. This recommendation highlights the importance of EWS vital sign documentation chart design.…”
Section: Documentationmentioning
confidence: 99%
See 3 more Smart Citations